Rancang Bangun Sistem Smart Greenhouse Berbasis IoT dengan Kendali Logika Fuzzy Menggunakan 4 Parameter Sensor - Chrisvan Simangunsong; Rijodi Simbolon; Menna Ginting (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The agricultural sector, particularly horticulture, faces significant challenges due to global climate change, causing unstable crop yields and quality. Traditional greenhouses in tropical regions often suffer from a heat trap effect, which induces plant stress if not properly managed. Current environmental control systems rely heavily on manual labor or simple on/off thresholds, leading to energy inefficiency and delayed responses. This study aims to design and simulate an internet of things (iot)-based smart greenhouse control system utilizing a fuzzy logic controller (flc) with the mamdani method. Unlike previous partial control studies, this research integrates four vital parameters simultaneously: air temperature, air humidity, soil moisture, and light intensity. The hardware architecture incorporates an esp32 microcontroller, dht22 and dht11 sensors, a capacitive soil moisture sensor, an ldr module, and actuators including a dc fan, water pump, and led grow lights. Simulation results using proteus software demonstrate that the fuzzy logic algorithm successfully regulates actuator speeds via pulse width modulation (pwm) based on environmental transitions, effectively preventing component chattering. Furthermore, the system successfully transmits real-time microclimate data to the blynk platform for remote monitoring. This integrated approach offers a more precise, energy-efficient, and adaptive solution for optimizing horticultural microclimates.